Music as Enculturation: The Holistic Relevance of John Blacking’s Perspective to Traditional Music Education in South Sulawesi - kurniawan, rahmat (GETER : Jurnal Seni Drama, Tari dan Musik, 2025)
This study examines the role of traditional music from South Sulawesi as a medium of enculturation in education, highlighting the relevance of John Blacking’s theoretical perspectives. The research is grounded in the phenomenon of declining interest among younger generations in traditional music only 19.4% of Generation Z express such interest due to limited facilities, insufficient early exposure, and perceptions of irrelevance to modern life. Employing a qualitative approach with a case study design, the research was conducted in formal educational institutions (SMA Negeri 10 Pangkep and SMAN 6 Jeneponto) as well as the Katangka Art Studio. Findings indicate that traditional music genres such as Sinrilik, Pakacaping, and Gandrang Bulo possess strong social, educational, and cultural functions, yet remain underutilized in teaching and learning contexts. Blacking’s concepts emphasizing universal musicality, the significance of early enculturation processes, and the intrinsic connection between music and its socio-cultural context provide a foundation for developing traditional music education that is more inclusive, relevant, and immersive. The study recommends a holistic approach that combines community-based learning, cross-arts and cultural integration, and active student participation, supported by government policy and community engagement, to ensure the sustainability of traditional music heritage in the face of globalization challenges